Multisensory therapy in letter reversal of dyslexic pupils - Subramaniam, Vijayaletchumy; Abdan Nasir, Nadia Shuhada (Horizon Research Publishing, 2020)
This research is conducted to examine the problem of letters reversal among dyslexic pupils. The purpose of this study is to describe the multisensory therapy to solve the problem. The study sample consisted of ten dyslexic pupils from Malaysia Dyslexia Association at Ampang, Kuala Lumpur who have serious letters reversal problems. In this study, the researcher limited the problem to reversal of letters of similar shape, namely /b/, /d/, /p/, /q/, /m/, /w/, /n/ and /u/ based on Levinson's Dyslexia Theory Syndrome (1994). In addition, a multisensory approach is used to solve the problem. This research uses observation, interviews and questionnaires methods. The research tools used are questionnaires and field notes. The results show that all the subjects in this study had the letter reversal problem of the eight letters, but the types of the letters that were reversed are different depending on the individuals. To solve this problem, the researchers developed ten therapies using multisensory approach and found that all of the therapies were able to solve the problem of letters reversal among the subjects. Through this research, teachers and parents can know the type of letters reversal among dyslexic pupils. This study also helps educators and parents plan appropriate and effective activities in solving the problem of the letters reversal that faced by their pupils and their children.